O coordenador pedagógico no processo de ensino aprendizagem - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The pedagogical coordinator is a professional of great relevance in the school environment, as he is considered a professional with a multifaceted and essential role for the proper functioning of educational institutions. This study aims to analyze the field of activity of the pedagogical coordinator in the teaching-learning process. The methodology used was bibliographical research in books and scientific publications on the subject. It was found that the role of the pedagogical coordinator is categorized into three main dimensions: articulating, formative and transformative, which covers different aspects of the coordinator's work and highlights the breadth of their responsibilities and impact on the school environment. Its functions are focused on supervising the teacher's work, managing available resources, preparing and implementing the school curriculum, monitoring students, in addition to promoting a harmonious relationship between all members of the school community, including parents, students, teachers and other employees. It was concluded that the role of the pedagogical coordinator as a facilitator, articulator and teacher trainer contributes to the construction of a collaborative, innovative educational environment aligned with the school's pedagogical objectives.
Keywords: Coordenador Pedagógico; Facilitado; Articulador; Formador; CNPQ:: CIÊNCIAS HUMANAS